A comparative study on monitoring of bioactive compound production/degradation, volatile substances, and oxidation indices during horn and bath high-power ultrasound-assisted oil bleaching - Mehran Sayadi; Elahe Abedi; Malihe Keramat (Ultrasonics Sonochemistry)
This research aimed to investigate and compare the effect of bath and horn ultrasound-assisted bleaching of sunflower oil on the degradation of tocopherols and sterols, production of volatile substances, and oxidation indices, including thiobarbituric acid (TBA) and peroxide value (PV) and with that of the industrial bleaching process. Ultrasonic bath and ultrasonic horn bleaching techniques reduced sunflower oil’s total tocopherol and total sterol contents to a greater extent than conventional bleaching techniques. While bath and horn sonication operated theoretically equivalent power settings, power meter measurements demonstrated that the bath sonicator delivered significantly less power than the horn sonicator. Among the ultrasonic bleaching techniques, the ultrasonic bath at 400 W showed the lowest reduction in total tocopherols, sterols and volatile compounds compared to the ultrasonic horn technique at the same theoritical power. Moreover, Despite the 800 W bath sonicator having significantly higher nominal power than the 400 W horn sonicator, the horn sonicator was considerably more effective at degrading bioactive compounds. Higher degradation of bioactive compounds coincided with increasing patterns in primary and secondary oxidation indices and volatile compounds in horn compared to bath and industrial bleaching due to the direct effect of ultrasonic horn and free radical formations.